Admission Hyperglycemia is Associated with Global Registry of Acute Coronary Events Score and Complications Following Acute Myocardial Infarction During 1-Year Follow-Up. (February 2022) - Qin, Yuhan; Qiao, Yong; Wang, Dong; Tang, Chengchun; Yan, Gaoliang
We explored the effect of admission hyperglycemia (AH) on the Global Registry of Acute Coronary Events (GRACE) risk score and major adverse cardiovascular and cerebrovascular event (MACCE) incidence during 1-year follow-up in acute myocardial infarction (AMI) patients. In this retrospective observational study enrolling 1098 AMI patients, hyperglycemia was defined as blood glucose level ≥180 mg/dl at admission. Overall, 158 and 84 patients of 272 diabetic and 826 non-diabetic patients were diagnosed with AH, respectively. Glucose levels at admission were closely associated with the GRACE score in patients with/without diabetes. MACCEs occurred in 222 patients; patients with AH showed significantly higher MACCE incidence (28.1%). Multivariate Cox logistic regression analysis indicated that AH was an independent risk factor for 1-year MACCEs. Subgroup analysis demonstrated that hyperglycemia increases MACCE risk in non-diabetic patients but not in diabetic patients. The admission glucose level combined with GRACE risk score showed a certain predictive value for MACCE incidence according to ROC analysis (OR = 0.798, p < .001). AH was strongly associated with a higher GRACE risk score in ST-segment elevation myocardial infarction patients. Thus, AH was an independent risk factor and had a high predictive value for MACCE during 1-year follow-up after AMI.